(untitled) (American Journal of Islam and Society, 1991)
The task undertaken in this book, the development of a “third approach” to the issue of women’s oppression superceding both feminism and traditionalism, is much needed and much neglected in the Islamic movement. Specifically, Ahmad analyzes the impact of the introduction of hudud (Islamic penal code) laws in Pakistan and makes policy recommendations for their reform. Although his analysis is not limited in usefulness to Pakistan, it is limited, however, by several shortcomings in argument, structure, and language. Ahmad’s strong points emerge in his empirical study of Pakistani family law. While he attempts to refute the criticism that the hudud laws discriminate against women, he also recognizes that the application of these laws in a legal patchwork fraught with contradictions has not helped women. For example, the Family Laws Ordinance of 1961 requires all marriages to be officially reported but, with common and Islamic opinion being contrary, this law is frequently neglected. So when the hudud laws of 1979 made adultery punishable, women living in Islamic but unreported marriages were reported for adultery by vengeful ex-husbands. This particular problem would be solved, Ahmad argues, by punishing such men for slander, a neglected aspect of the Shari‘ah’s approach to adultery which is to women’s advantage. He argues for an end to “this vicious circle of immediacy, adhocism and temporary solutions” (p. 48) in the application of the Shari‘ah, and for a more creative, comprehensive reform. His use of statistics from Pakistani courts is an attempt to ground his analysis in the living reality of Pakistani women, an attempt which is only infrequently made by Islamist writers on women’s issues, who usually hide behind obscure generalizations about the ideal society. It is also edifying to see an Islamist writer admit that “we should not doubt the intent and motive of those who talk on these issues and take a different position” (p. 11). Too often this debate over the status of women results in bitter and useless finger-pointing in which the advocates of change in women’s conditions are labelled “Western,” as if one had to be Western to see anything exploitative about the present treatment of Muslim women. Unfortunately, Ahmad does not stick to his promise and succumbs to a defensive diatribe against his ideological opponents, calling them ‘‘crypto-colonialists’’ and emphasizing their emergence from the upper classes. The same charge ...